Global masculinities and manhood - Jackson, Ronald L., 1970-; Balaji, Murali, 1979- (University of Illinois Press, 2011)
Bringing together an array of interdisciplinary voices, Global Masculinities and Manhood examines the concept of masculinity from the perspectives of cultures around the world. In the era of globalization, masculinity continues to be studied in a Western-centric context. Contributors to this volume deconstruct the history and politics of masculinities within the cultures in countries including Jamaica, Turkey, Peru, Kenya, Australia, and China. Scholars grapple with the complex politics of identity and the question of how gender is interpreted and practiced through discourse. Topics include how masculinity is affected by war and conflict, defined in relation to race, ethnicity, and sexuality, and expressed in cultural activities such as sports or the cinema. Contributors are Bryant Keith Alexander, Molefi K. Asante, Murali Balaji, Maurice Hall, Ronald L. Jackson II, Shino Konishi, Nil Mutluer, Mich Nyawalo, Kathleen Glenister Roberts, Margarita Saona, and Kath Woodward.